ANALISIS EFEKTIVITAS PELUNASAN HUTANG PAJAK DI KANTOR PELAYANAN PAJAK PRATAMA BITUNG - Tania, Beauty Theresia; Karamoy, Herman; Rondonuwu, Sintje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Tax liability represents accrued taxes including administrative sanctions in the form of interest, penalty or increment stipulated in tax assessment letters or similar letters under the provisions of the transitional tax laws. Implementation of tax liability in Bitung City is caused by external factors of taxpayers and internal factors of the fiskus (Tax Officers). This study aims to determine the effectiveness of tax repayment in KPP Pratama Bitung. The method of analysis used in this research is descriptive qualitative by using ratio of effectiveness ratio. The results of the researchand analysis show that the repayment of tax debt in KPP Pratama Bitung can be seen from the year 2013, 2014, 2015 the realization of the tax debt repayment did not reach the target and ini 2016, 2017 the realization of the debt repayment past the expected target. Based on the results of the analysis, the repayment of tax debt in KPP Pratama Bitung in 2013 is quite effetive, 2014 and 2015 ineffective, 2016 and 2017 are very effective..Keywords: Effectiveness, Tax Payable